TECOVIRIMAT: A COMPREHENSIVE REVIEW OF NOVEL DRUG FOR MONKEYPOX DISEASE - SHUKLA, AJAY KUMAR; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2023)
Orthopoxvirus infections caused by pathogenic agents require therapeutic intervention. Animal models of orthopoxvirus disease are crucial for assessing the effectiveness of antiviral medications and determining the right dose and duration of treatment in the absence of disease-affected individuals. Antiviral drugs for the treatment of severe orthopoxvirus infections have been developed as a result of research on smallpox preparedness. Concerns for the public's health have been raised by the monkeypox virus, a new zoonotic orthopoxvirus that can infect humans and produce a serious, contagious illness. An infection with the monkeypox virus causes a systemic, febrile rash condition that resembles smallpox in many ways. Monkeypox virus is an emergent human pathogen. It can nonetheless result in severe morbidity and mortality in humans while being less deadly than smallpox. In this review, we have explored a new antiviral drug, Tecovirmat. This drug prevents the development of the extracellular enveloped virus required for cell-to-cell transmission. It acts by limiting the production of egress-competent enveloped virions, which are necessary for the virus's spread within the host, by decreasing the action of the orthopoxvirus VP37 envelope-wrapping protein. It was approved by US-FDA for the treatment of smallpox as per Animal Rule, which bases marketing approval on a product's effectiveness in pertinent animal models.